2020
DOI: 10.1002/ange.202011480
|View full text |Cite
|
Sign up to set email alerts
|

Molekulare Zinkhydridkationen [ZnH]+: Synthese, Struktur und CO2‐Hydrosilylierungskatalyse

Abstract: DurchP rotonolyse von [ZnH 2 ] n mit der konjugierten Brønsted-Säure der Amine TMEDA(N,N,N',N'-Tetramethylethan-1,2-diamin) und TEEDA(N,N,N',N'-Tetraethylethan-1,2-diamin) kann das Zinkhydridkation [(L 2)ZnH] + , entweder als monomeres THF-Addukt [(L 2)ZnH(thf)] +-[BAr F 4 ] À (L 2 = TMEDA; BAr F 4 À = [B(3,5-(CF 3) 2-C 6 H 3) 4 ] À) oder als Dimer [{(L 2)Zn)} 2 (m-H) 2 ] 2+ [BAr F 4 ] À 2 (L 2 = TEE-DA), synthetisiert werden. Im Gegensatz zu [ZnH 2 ] n sind die kationischen Zinkhydride thermischstabil und in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29][30] Catalyticr eductiono f carbon dioxide through catalytic hydrosilylation [31][32][33][34] and, to some extent, hydroboration [35,36] with zinc catalysts has been investigated. [37][38][39][40][41][42][43][44] Zinc acetate is known to hydrosilylateC O 2 to am ixture of reduced products:s ilyl formates, bis(silyl) acetals, methoxysilanes, and methane. [45] Thee mergence of neutral and cationic molecular zinc alkyls and hydrides have provided more options for CO 2 hydrosilylation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26][27][28][29][30] Catalyticr eductiono f carbon dioxide through catalytic hydrosilylation [31][32][33][34] and, to some extent, hydroboration [35,36] with zinc catalysts has been investigated. [37][38][39][40][41][42][43][44] Zinc acetate is known to hydrosilylateC O 2 to am ixture of reduced products:s ilyl formates, bis(silyl) acetals, methoxysilanes, and methane. [45] Thee mergence of neutral and cationic molecular zinc alkyls and hydrides have provided more options for CO 2 hydrosilylation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have shown that zinc hydridesc atalyze CO 2 hydrosilylation, resulting in selective reductiont os ilyl formates or methoxysilanes. [43,46] Mechanistic studies have revealedt hat molecular zinc hydrides insert CO 2 across ZnÀHb ond. The resulting formate ZnÀ OC(H)Oreacts with the hydrosilane through s-bond metathesis involving ZnÀOa nd SiÀHb onds, regenerating the zinc hydride catalyst accompanied by the displacemento fs ilyl formate.…”
Section: Introductionmentioning
confidence: 99%